Terramechanics and OffRoad Vehicle Engineering, Second Edition: Terrain Behaviour, OffRoad Vehicle Performance and Design - Wong, J. Y. (Butterworth–Heinemann, 2012)
This book will be of great interest to any professional engineer or automotive engineering student working on off-road vehicles. Reflecting the increase in off-road vehicle production and development-recreational, agricultural, construction, military-this book equips readers with all of the necessary knowledge to successfully design and model off-road vehicle systems, and provides a comprehensive introduction to terramechanics, the mechanics of vehicle/terrain interaction